The history of negation in the languages of Europe and the Mediterranean. - Willis, David W. E.; Lucas, Christopher; Breitbarth, Anne, 1976- (Oxford studies in diachronic and historical linguistics ;, 2013)
This is the first volume of a two-volume comparative history of negation in the languages of Europe and the Mediterranean. It integrates typological, general, and theoretical research documents patterns and directions of change in negation across languages, and examines the linguistic and social factors that lie behind such changes.